Constituintes sangüíneos de vacas das raças Nelore (Bos indicus) e Holandesa (Bos taurus) e de bubalinas (Bubalus bubalis) da raça Murrah durante a gestação, no dia do parto e no puerpério - Fagliari, J. J.; Santana, A. E.; Marchio, W.; Campos, E.; Curi, P. R. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1998)
Blood constituents of Nelore, Hosltein and buffalo cows were determined during pregnancy, at the time of calving and at post-partum. It was verified that. 1. The pregnancy and post-partum periods had no influence in the erythrocyte values, but at calving the red blood cell counts and hemoglobin levels of Holstein and buffalo cows were lower than for Nelore cattle; 2. leukocyte counts were similar among groups; 3. total protein levels of Nelore cows were lower than Holstein and buffalo. The albumin levels were rite lowest at rite time of calving compared to late pregnancy; 4. glicose levels were lower ill buffalo cows during pregnancy as compared with Holstein cows. The glicemia of Nelore cows was lower as compared to Holstein cow's irt late pregnancy; 5. urea and creatinine levels were higher in buffalo cows than cattle. The urea and creatinine levels were greater in buffalo cows with maximum values at the post-partum and at the parturition, respectively; 6. bilirrubin levels were higher in bovine than buffalo cows; 7. aspartate aminotransferase activity was greater in buffalo cows and increased at the time of calving; 8. alkaline phosphatase activity was increased during pregnancy and decreased after the time of calving; 9. gammnglutamyltransferase activity,vas the highest for buffalo cows after calving; IO. calcium levels were the highest for Holstein cows at the post-partum and the phosphorus levels were higher in buffalo cows, which had the highest magnesium levels at the parturation.
Blood constituents of Nelore cattle (Bos indicus), Holstein cattle (Bos taurus) and Murrah buffalo (Bubalus bubalis) cows during pregnancy, at the time of calving and at post-partum
Keywords: pregnancy; calving; blood constituents; cattle; buffalo